Author's Strategies of Coverage of Military Conflicts in the Works of J. Cercas (Based on Literary Works and Journalistic Articles) - Артемова, Людмила Василівна (Київський національний університет імені Тараса Шевченка, 2025)
Our research is focused on the comparative study of the narrative strategies of J. Cercas as a novelist and columnist. As a starting point, we have used the theme of war in his literary work (the Spanish Civil War) and in his columns (the war in Ukraine) in ‘El País Semanal’. We have come to discover that one of Cercas’s strategies is to contrast ideas at different textual levels in order to reveal different approaches. In the structure of the column, this strategy is revealed in the contrastive use (antithesis) of ‘I/we’ VS ‘the other/they’. ‘We’ is used both to refer to the writer with his circle of loyal readers, and ‘we – the Spaniards’, ‘we – the Europeans (including Ukrainians)’. On the syntactic level, we can see the parallel structures skillfully used by the author, which, as a counterpart, are invested in semantic oppositions. Thus, war is contrasted with peace, truth with lies. Among the concepts that we have included in this research that are so closely linked to the theme of war are homeland, patriotism and patriot.

Наше дослідження ґрунтується на порівняльному вивченні наративних технік Х. Серкаса як прозаїка та колумніста. За відправну точку ми взяли тему війни в його літературній творчості (громадянська війна в Іспанії) та колумністиці (війна в Україні) в «El País Semanal». Ми виявили, що однією зі стратегій Серкаса є протиставлення ідей, антитеза на різних текстових рівнях з метою розкриття різних точок зору. У композаційній структурі колонки ця стратегія проявляється у використанні різних технік наративу, а саме протиставлення «я/ми» VS «інший/вони». Під «ми» розуміється як письменник з його колом читачів-однодумців, так і «ми – іспанці», «ми –європейці (українці включно)». На синтаксичному рівні бачимо майстерно використані автором паралельні конструкції, на які накладаються смислові опозиції, антитези. Відтак, війна протиставляється миру, а правда – брехні. Серед понять, які ми долучили до матеріалів цієї публікації, є тісно пов’язані з темою війни батьківщина, патріотизм і патріот.

Nuestra investigación está centrada en el estudio comparativo de las estratégias de J. Cercas como novelista y columnista. Del punto de partida nos ha servido el tema de guerra en su obra literaria (la Guerra Civil española) y en sus columnas (la guerra en Ucrania) en “El País Semanal”. Hemos llegado a descubrir que una de las estrategias cercasianas es la contraposición de ideas a diferentes niveles textuales con el objetivo de desvelar diferentes enfoques. En la estructura de la columna dicha estrategia se revela en el uso contrastivo de “yo/nosotros” VS “el otro/ ellos”. Bajo “nosotros” se entiende tanto el escritor con su círculo de lectores fieles, como “nosotros – los españoles”, “nosotros – los europeos (ucranianos incluidos)”. A nivel sintáctico podemos ver las estructuras paralelas hábilmente usadas por el autor que, como contrapartida, van investidas en las oposiciones semánticas, las antítesis. Así, guerra se contrapone a paz, verdad, a mentira. Entre los conceptos que hemos incluido en esta investigación que tan estrechamente van ligados al tema de guerra son patria, patriotismo y patriota.
Авторські стратегії висвітлення військових конфліктів у творчості Х. Серкаса (на матеріалі літературних творів і публіцистичних статей)
Estrategias del autor para enfocar conflictos militares en las obras de J. Cercas (basadas en obras literarias y artículos periodísticos)
Keywords: війна; техніка наративу; авторська стратегія; паралелізм; антитеза; war; narrative techniques; the author’s strategy; parallelism; antithesis; guerra; técnicas narrativas; estrategia del autor; paralelismos; antítesis